If it's not what You are looking for type in the equation solver your own equation and let us solve it.
19=6s-9s
We move all terms to the left:
19-(6s-9s)=0
We add all the numbers together, and all the variables
-(-3s)+19=0
We get rid of parentheses
3s+19=0
We move all terms containing s to the left, all other terms to the right
3s=-19
s=-19/3
s=-6+1/3
| f/4-15=5 | | 12.93+0.09m=13.42-0.13m | | 9h+7=16 | | 2(4x+5)=-48+2 | | -4+3x=-2x-14 | | -6r-3r=28 | | x-6=−3x | | -1-5x=6-6x | | 6x-8=5x+0 | | 1.5^x=1.23 | | 17=-8+9(a+5) | | 5-5x=11-4x | | -1(2x-4)=4.2x | | 22x-9+2x+16= | | f/4-15=15 | | 4x+6=-2(2x-5) | | -3y+48=4(y-2 | | 8z+7-5z=-24 | | 10y+8=4y+7 | | 12x-6=-4x-2 | | 18.26=3g+3.89 | | -16x–2=46 | | 7(5y-8)=29 | | 1−(2x+4)=−4x+5 | | 4(d-2)=4d | | -3(6d+8)=18+4d | | 16x-4=2x+14 | | 16-4=2x+14 | | -4x-37=-10x+53 | | -2v+9=3(-5v-6) | | 61=12x+8-2x | | h/3+9=27 |